Study Of Serum Triglyceride And Ldl-cholesterol Among Patients Suffereing From Liver Cirrhosis And Its Relation With Severity of The Disease (Central Medical College Journal, 2022)
Background: Cirrhosis is characterized by abnormal structure and function of the liver. Liver synthesizes the various lipoproteins involved in transporting cholesterol and lipids throughout the body. This makes liver an important site for lipid metabolism as well as its transport. Thus liver cirrhosis is associated with lipid abnormalities and the amount of decrement is expected to be significantly correlated with increasing severity of liver damage.Aims and objectives: To determine serum TG and LDL-C in patients with cirrhosis and study their relationship to the severity of cirrhosis.Materials & Method: This cross-sectional study was carried out in the Department of Biochemistry, Sylhet MAG Osmani Medical College, Sylhet during the period from January to December 2016. Fifty cirrhosis of liver patients fulfilling the inclusion criteria were enrolled as group-A and 50 age-sex matched healthy adults were selected as the control group (group-B).Result: Fasting serum TG and LDL-C were estimated. Severity of liver Cirrhosis was categorized according to Child-Pugh scoring system and increasing severity was categorized as Child Pugh class A, B and C. TG and LDL-C were decreased in patients with liver cirrhosis. The level of severity of liver damage significantly affects the serum LDL-C level in cirrhosis; and may be considered as marker of severity of liver damage in cirrhosis.Conclusion: It may be concluded that hypolipidemia exists in patients with liver cirrhosis and screening for severity of cirrhosis by LDL-C is important for intervention with appropriate therapy to reduce the severity of the disease.Central Medical College Journal Vol 5 No 1 Jan 2021 PP 25-29